The Livestock Sector in Colombia: Toward a Program to Facilitate Large-Scale Adoption of Mitigation and Adaptation Practices - Tapasco, Jeimar; LeCoq, Jean Fraçois; Ruden, Alejandro; Rivas, Juan Sebastián; Ortiz, Javier (Frontiers in Sustainable Food Systems, 2019)
Livestock raising is an important sector of the Colombian economy, which will face serious challenges in the next decade, including adaptation to and mitigation of climate change. Colombia must change the model of livestock production in a very short time by freeing up areas of pasture for other uses and focusing intensified livestock production in suitable zones. Despite the urgency and the magnitude of the required changes, only isolated small-scale initiatives exist. Colombia therefore has the challenge to scale-up these initiatives1, but at present it has no program designed to achieve this objective. We started by analyzing the policies, actors, and existing initiatives in Colombia. We then sought to understand the potential for and the limitations to scaling-up promising initiatives to face the challenges of climate change in the livestock sector. We identified the key elements from previous initiatives and classified them into the conceptual spaces identified in the theory of scaling-up. These are the spaces in matters of: policy, fiscal and financial matters, institutional capacity, learning, partnerships, and technical matters, emphasizing the importance of the technical dimension. Finally, we propose some elements for the design of Colombia's national program of livestock raising.